Cerebellar Kv3.3 potassium channels activate TANK-binding kinase 1 to regulate trafficking of the cell survival protein Hax-1 - Yalan Zhang (Nature Portfolio, 2021)
How the activity of the neuronal Kv3.3 voltage-dependent channel is regulated is unclear. Here, the authors show that the known Kv3.3 channel complex with Hax1, which affects spinal cerebellar ataxia, regulates the enzyme Tank Binding Kinase 1, modulating survival of cerebellar neurons.